Economic growth and transition : econometric analysis of Lim's S-curve hypothesis - Sng, Hui Ying (2008)
Professor Lim Chong Yah's S-Curve hypothesis is a simple yet highly insightful theory. By augmenting the mathematical and econometrical sophistication of the hypothesis, this thesis extends the S-curve hypothesis to provide furhter insights into economic growth and transition. The four core chapters in this thesis are closely related yet distinctly different, each dealing with a separate aspect of the S-Curve hypothesis.